Relationship Between Body Mass Index and Male Infertility at Kasih Ibu General Hospital Denpasar - Amelia Heryanto; I Gusti Ngurah Pramesemara; Yukhi Kurniawan; I Gusti Ayu Widianti (Universitas Airlangga, 2022)
Infertility can occur in men, characterized by the inability to make pregnancy in the partner. The causes of male infertility are multifactorial, one of which is obesity. Obesity parameter by body mass index >25 kg/m2. This study purposes of determining the relationship between obesity with body mass index measurement and male infertility. This type of research is an analytical cross-sectional study. This research was located at the Kasih Ibu General Hospital Denpasar. Purposive sampling was chosen as the sampling technique. The samples were 50 male patients aged 25-45 years who checked themselves at the Kasih Ibu General Hospital Denpasar between January and December 2020. All research data could be seen from the patient's medical records. The Pearson Chi-Square test was used to analyze the data. The results were 26 subjects (52%) with BMI >25 kg/m2 (obese) and 24 subjects (48%) with BMI <25 kg/m2 (non-obese). About 28 subjects (56%) were infertile, and 22 subjects (44%) were fertile. This study found that body mass index was significantly associated with infertility in male patients at Kasih Ibu General Hospital Denpasar. Obese men had a 2,308 higher risk of infertility than men were not obese (p = 0.002, RR = 2.308 (CI95% 1.262-4.220). The study has found that obesity may contribute to the event of male infertility. For further research should use a larger sample size to make it more accurate in population.